Protecting Children’s Rights in the Digital World: An Ever-Growing Challenge - Zaid Ali Zaid; Dr. Driss Ed.daran; Dr. Malik Zia-ud-Din (Al-Qanṭara, 2023)
The purpose of this study is to draw attention to the rise of electronic recruiting in today's technologically advanced society and the effects it has on the employer and the workers, who are mostly youngsters. Everyone under the age of 18 will be considered a kid for the purposes of this study. The numbers in this study are up-to-date since they were culled from the most recent studies and published in scholarly publications. For a more complete picture, this research also examines the pros and cons of electronic recruiting for minors. Rising living expenses and relative poverty have led many youngsters to seek employment opportunities as early as the Industrial Revolution. But, the introduction of modern technologies has altered the time-honored methods of employment and recruiting. Hence, companies from all over the globe have asked youngsters who are now enrolled in schools, colleges, or universities and have access to laptops or other devices to work for these businesses. Now LinkedIn, the industry's foremost platform for hiring and recruitment, has made it possible for kids as young as 13 to create professional profiles and adapt resumes accordingly. The report then discusses the perspective of the United Nations on this recruiting in light of human rights legislation. Statistics, facts, and legislation included in the study are drawn from a variety of academic publications and the Universal Declaration of Human Rights, which served as the primary source for the research technique (UDHR).